“We Become a Madman to Be Calmed”—Patients’ Voices: Crossing the Threshold of Psychiatric Emergency Departments - Meriaux, Mathilde; Denis, Jennifer (Frontiers in Psychology, 2021)
Crossing the threshold of a psychiatric emergency room is a real ordeal. It is a passage that upsets, worries and sometimes paralyzes. However, it can also become an opportunity if psychological suffering is welcomed, accepted and understood. The welcome is the starting point for care. Our objective is to understand the meaning given to the phenomenon of being welcomed by patients experiencing psychiatric emergencies. The research is based on Grounded Theory Methodology (Glaser & Strauss, 1967) to explore and understand the complexity of the phenomenon. The results reveal that being welcomed can be considered as a rite of passage taking place in four successive phases, which are themselves organized into four interactive dimensions. The welcome as a rite of passage constitutes a powerful psychic support which arranges the transitional space in which the individual finds themself, and accompanies the identity transformations, the anguish, and the various sufferings which are not lacking in these moments of crisis